2012
DOI: 10.1097/tp.0b013e3182692ad2
|View full text |Cite
|
Sign up to set email alerts
|

Non-HLA Antibodies Targeting Vascular Receptors Enhance Alloimmune Response and Microvasculopathy After Heart Transplantation

Abstract: Elevated levels of AT(1)R and ET(A)R Abs are associated with cellular and Ab-mediated rejection and early onset of microvasculopathy and should be routinely monitored after heart transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
117
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(119 citation statements)
references
References 29 publications
2
117
0
Order By: Relevance
“…A following study detected a strong association between the presence of AT1R-Abs and AMR in kidney transplanted recipients whose sera contained no antibody to donor HLA or MICA [8]. A recent pilot study in a small cohort with 30 recipients in the first year after HTx showed a correlation of elevated levels of AT1R-Abs and ETAR-Abs with early onset of microvasculopathy at month 12, and graft loss following HTx, implicating relevant effects on post-transplant morbidity and mortality in that study [10]. Higher levels of AT1R-and ETAR-Abs were observed in patients with acute cellular rejection and antibodymediated rejection at months 1 and 12 post-HTx [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A following study detected a strong association between the presence of AT1R-Abs and AMR in kidney transplanted recipients whose sera contained no antibody to donor HLA or MICA [8]. A recent pilot study in a small cohort with 30 recipients in the first year after HTx showed a correlation of elevated levels of AT1R-Abs and ETAR-Abs with early onset of microvasculopathy at month 12, and graft loss following HTx, implicating relevant effects on post-transplant morbidity and mortality in that study [10]. Higher levels of AT1R-and ETAR-Abs were observed in patients with acute cellular rejection and antibodymediated rejection at months 1 and 12 post-HTx [10].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, antibodies targeting against other non-HLA antigen like the angiotensin II type 1 receptor (AT1R) and the endothelin receptor A (ETAR), have shown to play a role in several severe alloimmune and autoimmune pathologies ranging from renal allograft rejection [8] to microvasculopathy in systemic sclerosis [9] and in cardiac transplants [10].…”
Section: Introductionmentioning
confidence: 99%
“…Hiemann et al 5 reported in their pilot study that patients on assist device support before heart transplantation were more likely to develop high anti -AT1R antibody levels (43% of supported versus 18% of non -supported patients, P = 0.021) within 24 h after heart transplantation, implicating pre -transplant sensitization. Barten el al.…”
Section: Discussionmentioning
confidence: 99%
“…The negative impact of anti -HLA antibodies on post -transplant allograft function and survival has now been well documented. Recently, there has been accumulating evidence of various non -HLA antibodies involvement in decreased allograft and recipient survival [5][6][7][8][9][10] . While anti -HLA antibodies exert their negative effect via complement activation and antibody -mediated cytotoxicity, antibodies against AT1R, act as a natural allosteric receptor agonist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation